In Search of the Culprit : Aspects of Medieval Authorship. - Rösli, Lukas. (Andere Ästhetik - Studien Series, 2022)
The book series Andere Ästhetik - Studien (AÄS) (Different Aesthetics - Studies) mainly comprises monographs and collections of scholarly articles that address the research programme of the Collaborative Research Centre 1391 in a disciplinary perspective.